2014
DOI: 10.1039/c4fo00446a
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mastication, salivation and food bolus formation on salt release during bread consumption

Abstract: Health authorities recommend higher fibre and lower salt content in bread products. However, these basic ingredients of bread composition are multifunctional, and important changes in their content influence the texture, flavour and acceptability of the product. This study was designed to investigate the link between oral processing, bolus formation and sodium release during the consumption of four different breads that varied in composition and structure. Chewing behaviour was determined by surface electromyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 62 publications
(154 reference statements)
2
35
0
Order By: Relevance
“…Finally, the saliva uptake for a given bread was found to depend on individuals, which demonstrated the inter-individual differences in salivary behaviour, as already reported in a previous study of bread. 16 We also observed changes in salivary composition. Protein content increased significantly throughout the chewing process and depended on the bread.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Finally, the saliva uptake for a given bread was found to depend on individuals, which demonstrated the inter-individual differences in salivary behaviour, as already reported in a previous study of bread. 16 We also observed changes in salivary composition. Protein content increased significantly throughout the chewing process and depended on the bread.…”
Section: Discussionmentioning
confidence: 77%
“…In the case of bread, the understanding of food oral processing and bolus formation has been recently studied extensively. 7,[10][11][12][13][14][15][16][17] In particular, the presence of a thick and dry crust on bread (i.e., a French baguette) influences the chewing force, chewing duration, salivary uptake and bolus particle size and hardness compared to crumbs alone. 10,11 Wheat breads with higher density were found to require longer mastication times than wheat bread with a lower density.…”
Section: Introductionmentioning
confidence: 99%
“…This is highlighted particularly strongly by Tournier et al [44], who found significant inter-individual differences in the amount of saliva taken up by the bolus following mastication of bread. Mastication (number of chews) and salivation may adapt to the differences in composition and structure of the bread, although in this study it is difficult to distinguish the contributions from bread hardness, moisture content, taste and other parameters.…”
Section: Page 8 Of 20mentioning
confidence: 82%
“…A key observation from the recent literature is that the middle stages of oral processing is still not well understood beyond observations of agglomeration, moisture increases and a sensation of dryness/hydration [41*, 44,46]. In the later periods of oral processing, bolus rheology is considered important, but inter-individual differences make it challenging to quantify how it influences sensory perception.…”
Section: Discussionmentioning
confidence: 99%
“…First, no oral significant factor of dislike‐related selectivity score was revealed. This was quite surprising because we thought that the pleasure encountered, while eating would be influenced by the number of contacts existing between posterior teeth, which may be either the consequence of impaired taste sensitivity secondary to dental deafferentation or decreased flavour release from bolus fragmentation with reduced number of occluding teeth . Then, oral discomfort–related food selective behaviour was found to be closely dependent on oral health–related quality of life and occlusal status.…”
Section: Discussionmentioning
confidence: 97%